2008
DOI: 10.1158/1078-0432.ccr-08-1104
|View full text |Cite
|
Sign up to set email alerts
|

Phase I/II Study of G3139 (Bcl-2 Antisense Oligonucleotide) in Combination with Doxorubicin and Docetaxel in Breast Cancer

Abstract: Purpose Preclinical data showed enhancement of breast cancer cell death when G3139 was combined with anthracyclines and taxanes. We evaluated the efficacy and safety of a Bcl-2 antisense oligonucleotide, G3139, in combination with doxorubicin (A) and docetaxel (T) in patients with locally advanced breast cancer (LABC). Experimental Design Following a brief phase I to determine the phase II dose, patients with locally advanced breast cancer received G3139 administered by continuous i.v. infusion for 5 to 7 da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 27 publications
0
32
0
Order By: Relevance
“…In the present study, the use of WT1-RNAi, combined with doxorubicin and cisplatin, induced a synergistic effect on the inhibition of cell proliferation; similar results have been observed in vitro by other investigators with different antisense oligonucleotides and siRNA in different cell lines (31,38,39). Moulder et al reported that the combination of a Bcl-2-specific antisense oligodeoxyribonucleotide (G3139) with doxorubicin and docetaxel is feasible but has limited efficacy in patients with LABC, most likely due to the inability of G3139 to induce a biologically meaningful downregulation of Bcl-2 levels in primary breast tumors in a Phase I/II study (33). The combination therapy of asODNs and cytotoxic drugs has several potential advantages, including the ability to use lower doses of chemotherapeutic drugs, fewer side effects on normal cells and loss of chemoresistance.…”
Section: Discussionmentioning
confidence: 78%
“…In the present study, the use of WT1-RNAi, combined with doxorubicin and cisplatin, induced a synergistic effect on the inhibition of cell proliferation; similar results have been observed in vitro by other investigators with different antisense oligonucleotides and siRNA in different cell lines (31,38,39). Moulder et al reported that the combination of a Bcl-2-specific antisense oligodeoxyribonucleotide (G3139) with doxorubicin and docetaxel is feasible but has limited efficacy in patients with LABC, most likely due to the inability of G3139 to induce a biologically meaningful downregulation of Bcl-2 levels in primary breast tumors in a Phase I/II study (33). The combination therapy of asODNs and cytotoxic drugs has several potential advantages, including the ability to use lower doses of chemotherapeutic drugs, fewer side effects on normal cells and loss of chemoresistance.…”
Section: Discussionmentioning
confidence: 78%
“…The tumor-bearing mice were subcutaneously implanted with 0.1 mL of physiological saline containing 5×10 4 A549 cells in the left and right hind legs. Drug administration began when the tumor volume reached ~50-70 mm 3 (set as 0 days). The tumor-bearing mice were randomly divided into the following three groups: physiological saline, DOX/PTX, and PTX/DOX-LCP.…”
Section: In Vivo Anti-tumor Efficacymentioning
confidence: 99%
“…Drug combinations not only reduce the frequency and dosage of drug administration but also relieve drug resistance and improve therapeutic efficacy. 2,3 The combination of doxorubicin (DOX) and paclitaxel (PTX) is the most effective and common regimen in first-line lung tumor treatments. 4 It is worth noting that DOX and PTX possess different water solubility and action mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Small RNAs or chemicals targeting the anti-apoptotic genes are also on their way towards the prescription for breast cancer patients. However, as a pioneering anticancer nucleic acid drug, G3139-the antisense oligonucleotide targeting Bcl-2 showed limited therapeutic efficacy when combined with doxorubicin and docetaxel in phage I/II studies on breast cancers (Moulder et al, 2008). Inhibitors to poly(ADP-ribose) polymerase-1 (PARP-1), a welldefined substrate of caspase-3, have showed single agent activity in treatment of breast cancers in a phase I trial, and conferred therapeutic benefits in combination with chemotherapy in triple-negative breast cancers without an increase in normal tissue toxicity in a phase II clinical trial.…”
Section: Targeted Apoptosis In Clinical Treatment Of Breast Cancersmentioning
confidence: 99%